2018
DOI: 10.2478/dim-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

A Clickstream Data Analysis of the Differences between Visiting Behaviors of Desktop and Mobile Users

Abstract: Mobile devices are gaining popularity among online shoppers whose behavior has been reshaped by the changes in screen size, interface, functionality, and context of use. This study, based on a log file from a cross-border E-commerce platform, conducted a clickstream data analysis to compare desktop and mobile users’ visiting behavior. The original 2,827,449 clickstream records generated over a 4-day period were cleaned and analyzed according to an established analysis framework at the footprint level. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The detailed description of sessions, queries and browsing activities are provided in the "Results" section. Data collection periods of previous studies were referenced for comparison purposes (Baeza-Yates et al, 2007;Bai and Cambazoglu, 2019;Jiang et al, 2018;Kamvar et al, 2009;Li et al, 2009;Song et al, 2013). Compared to the time range of data sets from previous studies, it seemed that the present study with three months' of log session data could provide a substantially large and comprehensive data set.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The detailed description of sessions, queries and browsing activities are provided in the "Results" section. Data collection periods of previous studies were referenced for comparison purposes (Baeza-Yates et al, 2007;Bai and Cambazoglu, 2019;Jiang et al, 2018;Kamvar et al, 2009;Li et al, 2009;Song et al, 2013). Compared to the time range of data sets from previous studies, it seemed that the present study with three months' of log session data could provide a substantially large and comprehensive data set.…”
Section: Methodsmentioning
confidence: 99%
“…A few studies (Jiang et al, 2018;Song et al, 2013) investigated user click behaviours. Jiang et al (2018) analysed users' click behaviours of a Chinese e-commerce site and found that average page viewing duration of desktop users is longer than that of mobile users.…”
Section: Comparison Of Mobile and Desktop Search Behavioursmentioning
confidence: 99%
See 3 more Smart Citations